Abbreviation of preoperative fasting and malnutrition: impact on cost-effectiveness of surgical patients - WESLEY SANTANA CORREA ARRUDA; DIANA BORGES DOCK-NASCIMENTO; JOSÉ EDUARDO DE AGUILAR-NASCIMENTO (Revista do Colégio Brasileiro de Cirurgiões)
ABSTRACT Introduction: Abbreviating preoperative fasting improves clinical outcomes, such as reducing hospital stay, morbidity and postoperative mortality. However, there is a lack of data regarding the reduction of hospital costs. Therefore, the objective of the research was to analyze whether reducing preoperative fasting time with the provision of carbohydrate-rich liquid has an influence on hospital costs for surgical patients. Methods: Retrospective data were collected from patients undergoing surgical procedures at a University Hospital in 2019. The main outcome variable investigated was cost hospital in reais. Data such as gender, age, type of surgery, length of stay, nutritional data, and outcomes were also collected. Next, a comparative analysis of the variables was carried out in relation to patients who followed the preoperative fasting abbreviation protocol, with liquid rich in carbohydrates, and those whose protocol was not applied. Results: The mean (± standard deviation) fasting time of the study participants was 267.92±89.8 (range: 120-605) minutes in the group that shortened the fast and 768.6±247.8 (150 -1244) minutes in the group that did not perform the abbreviation (p<0.01). In relation to hospital costs, it was observed that patients who shortened their fasting had a lower average cost than those who did not shorten it (R$ 3,245.37±4,157.5 vs R$ 10,897.39±16,701.3; p< 0.01). They were shown to be significantly associated with higher cost, malnutrition and prolonged preoperative fasting. Conclusions: According to data from this study, shortening preoperative fasting reduces hospital costs. Corroborating prolonged fasting, malnutrition also makes hospitalization more expensive.